Development of a Scientific Writing Book based on TPACK to Support the Merdeka Belajar-Kampus Merdeka Program - Khairun Nisa; Yen Aryni (AL-ISHLAH: Jurnal Pendidikan, 2023)
This study aimed to develop a book for writing research articles based on TPACK that were valid, practical, and effective in supporting Merdeka Belajar-Kampus Merdeka (MBKM) program. This book contains technology recommendations that can be used in writing scientific articles and tutorials on how to use them. This development research used the Plomp development model, which consists of three stages, namely the preliminary research phase (early research phase), the development or prototype development phase (development phase), and the assessment phase (assessment phase). The data of this study were collected through observation, interviews, questionnaires, and tests of writing scientific articles for undergraduate students. Several documents used were questionnaires, observation sheets, and validation sheets. The data were analyzed by using Likert Scale. The result showed that Scientific Writing Book based on TPACK had met the validity, practicality, and effectiveness requirement to support Merdeka Belajar-Kampus Merdeka (MBKM) program.